2021
DOI: 10.3389/fpsyg.2021.769760
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Post Covid-19 Management Strategies and Policies in Hospitality and Tourism

Abstract: The strategic perspective of management policies gained utmost importance during the post-Covid era. The researchers are trying to introduce strategies that can help organizations cope with post-crisis destruction. Yet, the research on the topic is fragmented, mainly related to the hospitality and tourism industry. This manuscript aims to present scholarly research findings dealing with the post-Covid-19 management strategies in the hospitality and tourism industry from January 1, 2020, to July 28, 2021. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
0
15
0
3
Order By: Relevance
“…This was natural, since the term COVID-19 (and synonymous keywords that were grouped under this term) directly characterized the field of research. Literature review revealed that most bibliometric studies on COVID-19 (Alshater et al, 2021;Gan et al, 2021;Handoko, 2021;Islam et al, 2021;Khan et al, 2021;Utkarsh and Sigala, 2021;Okolie and Ogundeji, 2022;Singh and Verma, 2022) included COVID-19 or related keywords in co-word network maps. Furthermore, certain bibliometric studies (Nagy et al, 2021;Boonroungrut et al, 2022, Zhang et al, 2022 suggested that highly repeated general terms in co-word analysis does not have a meaning since they represent the entire field of research.…”
Section: Co-word Analysis Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was natural, since the term COVID-19 (and synonymous keywords that were grouped under this term) directly characterized the field of research. Literature review revealed that most bibliometric studies on COVID-19 (Alshater et al, 2021;Gan et al, 2021;Handoko, 2021;Islam et al, 2021;Khan et al, 2021;Utkarsh and Sigala, 2021;Okolie and Ogundeji, 2022;Singh and Verma, 2022) included COVID-19 or related keywords in co-word network maps. Furthermore, certain bibliometric studies (Nagy et al, 2021;Boonroungrut et al, 2022, Zhang et al, 2022 suggested that highly repeated general terms in co-word analysis does not have a meaning since they represent the entire field of research.…”
Section: Co-word Analysis Findingsmentioning
confidence: 99%
“…Thus, science mapping should be employed to visualize the interactions between the scientific items (authors, studies, journals, institutions, countries, concepts, citations) in the field, creating a map of the relevant literature (Block and Fisch, 2020). The review of social sciences literature would reveal that significant bibliometric studies were conducted on COVID-19 in the fields of economics (Mahi, Mobin, Habib and Akter, 2021;Nagy et al, 2021), business and management (Verma and Gustafsson, 2020), accommodation, leisure, sports and tourism (Andersson, Jansson, Karlén and Radmann , 2021;Khan, Nasir and Saleem, 2021;Utkarsh and Sigala, 2021), media and communication (Gan, Yaacob and Latif, 2021), and education (Karakose and Demirkol, 2021;Boonroungrut, Saroinsong and Thamdee, 2022;Zhang, Carter, Qian, Yang, Rujimora and Wen, 2022). Although Singh and Verma (2022) conducted a bibliometric review that included studies published in social sciences literature during the first six months of the pandemic, no sociological bibliometric study has been conducted specifically on COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis has been used in many disciplines to date, including psychology. For example, Khan et al (2021) conducted a quantitative analysis of articles on tourism and hospitality management strategies in the post-pandemic era. The results showed that relevant management strategies play an important role in helping managers respond to the survival and development of the post-crisis hotel and tourism industry.…”
Section: Introductionmentioning
confidence: 99%
“…This pandemic outbreak also had a significant adverse effect on the organization’s day-to-day processes. Organizations have implemented various tactics to survive this pandemic ( Khan et al, 2021a ). Many organizations are entirely out of the game, while some work online, providing vital services to the people impacted by the pandemic ( Asghar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%